Exploring the Impact of Driver Behavior on Customer Trust: A Study of Ride-Hailing Services in Malaysia - Teow Boon Keong; Ooi Lyn Liq; Nur Nazihah Binti Mohd Rodzi; Nur Irdhila Binti Mohd Zaki; Nur Natasha Binti Mohd Azlan; Nur Jannah Binti Abdul Manap; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2026)
As one of the leading ride-hailing and delivery service platforms in Malaysia, Grab connects customers with drivers through its mobile application. This study aims to examine the impact of driver behavior on customer trust among Grab customers and role of customer trust in shaping customer experiences. Additionally, it seeks to reveal how levels of trust and driver interactions influence customer experiences with Grab services in Malaysia. Data were collected through a cross-sectional quantitative survey using a Google Form with five-point Likert-scale questions from approximately 100 Grab users. The findings reveal that driver-related factors, including usefulness (b = 0.225, p .05), ease of use (b = 0.327, p .01), and convenience (b = 0.332, p .01), have significant positive effects on customer trust, while perceived risk has a negligible influence (b = ?0.010, p .05). These results highlight how trust shapes customer perceptions of driver behavior. The study concludes that positive driver behavior strengthens customer trust, emphasizing trust as a key mechanism through which driver interactions affect experiences. High trust levels lead customers to perceive interactions more positively, reinforcing confidence in the service. The findings suggest that Grab should prioritize trust-building strategies, including consistent driver training, improved communication, and transparent feedback systems, to strengthen customer relationships and ensure long-term customer loyalty.